Perfectionistic Traits, Competitive Anxiety, and Self-Esteem among Cricket Players - Kalsoom, Umme; Sarwar, Amina; Bibi, Maryam; Zahid, Hamna (Applied Psychology Review, 2025)
The current study aimed to determine the relationship between perfectionistic traits, competitive anxiety, and self-esteem in cricket players. It was hypothesized that; (a) There is likely to be a significant relationship between perfectionistic traits, competitive anxiety, and self-esteem in cricket players; (b) Perfectionistic traits and competitive anxiety are likely to predict self-esteem in cricket players; and (c) There is likely to be gender differences in perfectionistic traits, competitive anxiety, and self-esteem among cricket players. The study employed correlational research design and non-probability purposive sampling for data collection from (N=100) cricket players, both males (n=50) and females (n=50). The Frost Multidimensional Perfectionism Scale, Competitive Sport Anxiety Inventory-2, and Rosenberg Self-esteem Scale measures were used. Results showed a significant positive correlation between perfectionistic traits on the levels of high personal standards, and concern with precision (perfectionistic striving) and self-esteem. Whereas, self-esteem is significantly negatively correlated with concern over mistakes and doubts, and concern with parents (perfectionistic concerns). The results also showed a significant negative correlation between competitive anxiety and self-esteem. Additionally, the results also indicated that high personal standards (subscale of perfectionist traits) positively predict self-esteem, while worry concerns (subscale of competitive anxiety) negatively predict self-esteem. Furthermore, the results indicated significant gender differences between excessive concerns with parents and high personal standards. Females were higher on the level of concerns with parents and high personal standards than males. The current study would be helpful in providing the basis for further empirical research.